The cost-effectiveness of syphilis screening in pregnant women: a systematic literature review - Zhang, Meng; Zhang, Hongyan; Hui, Xiaoqing; Qu, Huimin; Xia, Junfen; Xu, Feng; Shi, Cannan; He, Junjian; Cao, Yuan; Hu, Mengcai (Frontiers in Public Health, 2024)
The cost-effectiveness study of syphilis screening in pregnant women has not been synthesized. The aim of this study was to synthesize the economic evidence on the cost-effectiveness of syphilis screening in pregnant women that might contribute to make recommendations on the future direction of syphilis screening approaches. We systematically searched Medline, PubMed and Web of Science for relevant studies published before January 19, 2023 and identified cost-effectiveness analyses for syphilis screening in pregnant women. The methodological design quality was appraised by Consolidated Health Economic Evaluation Reporting Standards (CHEERS) 2022 checklist. Seventeen literature met the eligibility criteria for a full review. Of the seventeen studies, four studies evaluated interventions using different screening methods, seven studies assessed a combination of syphilis testing and treatment interventions, three studies focused on repeat screening intervention, and four studies evaluated the interventions that integrated syphilis and HIV testing. The most cost-effective strategy appeared to be rapid syphilis testing with high treatment rates in pregnant women who were positive. The cost-effectiveness of syphilis screening for pregnancy has been widely demonstrated. It is more essential to improve the compliance of maternal screening and the treatment rates for positive pregnant women while implementing screening.